The Mental Space of Game in "Our Mother is an Enchantress" by Joanna Papuzińska - Olga Derkachova (Vasyl Stefanyk Precarpathian National University, 2016)
The article is devoted to the mental space of game in polish fairy tale Our Mother is an Enchantress by Joanna Papuzinska. Modeled reality in Papuzińska's book has a double-level structure consisting of the real world and fairy world, where children get involved with the help of their mother's game. The plot of the tale is shaped by an imaginary act of creating a special mental space of game.